Prediction of HIV mortality in Thailand using three data sets from the national AIDS program database - Hiwot D. Tulu; Apiradee Lim; Arinda Ma-a-Lee; Kanitta Bundhamcharoen; Nuttapat Makka (Penerbit Universiti Kebangsaan Malaysia, 2020)
HIV continues to hinder the growth and development of a country and identifying the mortality rate will help to address this problem. Therefore, we sought to examine HIV mortality in Thailand in the years 2014 and 2015. A retrospective study was conducted to investigate HIV mortality in all regions of Thailand. For the reliability of this study, the data were drawn from two main sources, Bureau of Registration and Administration (BORA) and the National Health Security Office (NHSO) of Thailand. A total of 23,243 deaths were recorded in years 2014 and 2015. Negative binomial regression was used to predict and compare HIV mortality rates by year, age group and gender. The overall HIV mortality accounted for 2.6% of all reported deaths, representing 18.3 deaths per 100,000 populations. Among HIV deaths, 91% of them participated in the National AIDS Program (NAP) and 56% of them received Antiretroviral Therapy (ART). There was statistically significant effect, with males having a higher death rates than females. Despite the relevance of reduction of HIV mortality in Thailand, our study clearly shows that HIV mortality in Thailand is much dependent on age and gender. Thus, we suggest continued effort is needed to address gender and age difference.